1999
DOI: 10.1007/s002340050832
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Wolfram syndrome (DIDMOAD)

Abstract: Wolfram syndrome (DIDMOAD) is a rare diffuse neurodegenerative disorder characterised by diabetes insipidus, diabetes mellitus, optic atrophy, deafness, and a wide variety of abnormalities of the central nervous system, urinary tract and endocrine glands. It may be familial or sporadic. Reported features on MRI of the brain are absence of the physiological high signal of the posterior lobe of the pituitary, shrinkage of optic nerves, chiasm and tracts, atrophy of the hypothalamic region, brain stem, cerebellum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 0 publications
3
29
0
1
Order By: Relevance
“…The deafness is sensorineural and degenerative. Atrophy of the vestibulocochlear nuclei and inferior colliculi may be responsible (15).…”
Section: Discussionmentioning
confidence: 99%
“…The deafness is sensorineural and degenerative. Atrophy of the vestibulocochlear nuclei and inferior colliculi may be responsible (15).…”
Section: Discussionmentioning
confidence: 99%
“…Because diabetic retinopathy is rare among Wolfram syndrome patients with poor visual acuity, neurological complications have been implicated (Seynaeve et al, 1994;Barrett et al, 1997). An MRI study of Wolfram syndrome patients has revealed atrophy of the optic nerves, chiasm, and tracts (Galluzzi et al, 1999). In addition, Wfs1 expression has been detected in retinal ganglion cells and optic nerve glia of cynomolgus monkey (Macaca fascicularis), suggesting a similar expression profile in humans (Yamamoto et al, 2006).…”
Section: Relationship Of Wfs1 Expression To Wolfram Syndromementioning
confidence: 97%
“…may also occur. It is, generally, a diffusion of the degenerative process which affects at first some nervous regions: optical nerve, posterior lobus of hypophysis, hearing ways, provoking visual deficit, diabetes insipidus, hearing loss and subsequently it spreads affecting also other structures (the brain stem, the cerebellum and the cerebral cortex) as demonstrated by MR study [25].…”
Section: Considerationsmentioning
confidence: 98%